Compliant vs convenient: is the Kansas State University campus truly user-friendly for persons with a physical disability? - Klingler, Ashley (Kansas State University, 2014)
The purpose of this thesis is to discover whether disability access regulations are being met and whether the regulations fulfill their intended purpose. Is Kansas State University Campus in Manhattan, Kansas ADA compliant (follows the current law) and convenient (user-friendly)? This inquiry can be split into two research questions: (1) Do the main entrances (entry experience being the sidewalk, ramp, and door) to buildings on the Kansas State University campus comply with current ADA guidelines? (2) Do students on campus find the access to these buildings user-friendly? This study has two main questions, and therefore multiple research methodologies: a focus group, audit, and guided activity. The focus group was made up of physically disabled students at KSU who are therefore familiar with access on the campus. The second method involved a yes-no checklist to test whether the buildings meet code. The third involved disabled and non-disabled students using a wheelchair for a day, with post-event survey to test public opinion of access on campus. My hypothesis anticipated that Kansas State University is code compliant, but not user-friendly. The conclusion is that no structure is fully sidewalk/ramp/door compliant, but two structures’ doors are fully compliant. According to the audit: ramps are mostly not needed (only 35 percent of structures need a ramp), sidewalks are 66 percent compliant, and doors are 63 percent compliant. According to the survey: doors are in the best condition, with ramps next, and sidewalks last. When comparing the checklist (compliance) and survey (convenience) results, sidewalk results were different, the ramp results were non-conclusive, and the door results were similar. This means that sidewalks meet code, but people do not find them accessible. Because ramps are not always needed, it made the checklist and survey difficult to compare. The analysis did not result in a clear “Similar” or “Different” result, therefore the comparison was non-conclusive. Doors were in the best condition on the checklist, and most people felt they were in good conditions. The application of this project allows other universities and communities to test whether their structures adequately provide access to students with a disability in a way that is user-friendly.
Keywords: Disability Access; Code Compliant; User-friendly; Kansas State University; Americans with Disabilities Act; Architecture (0729); Area Planning and Development (0341); Law (0398)